ANALISIS TEKNIS DAN EKONOMIS PENGOLAHAN ROTAN - Achmad Supriadi; D Martono; T Puspitodjati; O Rachman (Jurnal Penelitian Hasil Hutan, 2002)
Investigation the modified on processing of large-diameter rattan species, i.e. karokok (Calamus viminalis), seuti (Calamus ornatus), and lilin (Calamus spp.) originating from West Java has been conducted. in this regard, two alternatives of rattan processing were implemented, i.e. first alternative : fresh rattan -->flying --> sun-drying to air-dry condition -- > scropping ; and second alternative : fresh rattan --> preserving --> sun-drying to air-dry condition --> scrapping. The main aim of this investigation was to assess the resistance of ranan against blue-stain, the chief price of production, and the benefits as obtained from each of the two processing alternatives. Research results indicated That the occurence of blue-stain attack on rattan from the first alternative processing at 5.5 percent and 1. 7 percent intensity, respectively. Those percentages were much lower than the one in rattan industry implementing the conventional processing (i.e. 19 percent). Meanwhile. the durations of sun-drying stage required in the first and second alternatives were consecutively 9 days and 14 days. On the other hand. the scrapping time of both first and second alternatives were practically similar to each other (i.e 13 second for each piece of the corresponding rattan). Further, species of rattan and manner of processing (i.e. first and second alternatives) were interacted there by significantly affecting the rattan resistence the biological infestation attack and the processingproductivity.The chief price of rattan piece for the first and second alternatives were consecutively Rp 1. 640 and Rp 1.587. Meanwhile the priceforthe conventional rattan industry was Rp 1.825. Therefore. the theoritical gross benefits per piece of rattan for the first and second alternatives were Rp 860 and Rp 913. in addition, the added value of rattan from both alternatives was in the range of Rp 1.500- Rp 1.689.Based on the resistance of rattan against blue-stain, chief price of production and benefits, the second processing alternatives turned out to be technically and economically the best.